Politics and Defence Research in the Cold War - Turner, Jonathan (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2012)
The Defence Research Board (DRB) of Canada is an ideal case study for the operation and organization of science in government. The history of the DRB demonstrates the ebb and flow of government interest in science and defence from 1947 to 1977. This paper traces defence research through its most transformative events: demobilization, the Korean War, the International Geophysical Year, the Glassco Commission, the 1964 White Paper, integration and unification of the Department of National Defence, internal reviews, the 1971 White Paper, the Management Review Group, and the Lamontagne Committee. This sequence of transformative events reveals the importance of politics and personalities to decision-making, and the difficult alliance of scientists with soldiers.